2022
DOI: 10.1007/s11920-022-01346-z
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth-Based Delivery of Medication-Assisted Treatment for Opioid Use Disorder: a Critical Review of Recent Developments

Abstract: Purpose of Review Telehealth-delivered medication-assisted treatment for opioid use disorder (tele-MOUD) has received increased attention, with the intersection of the opioid epidemic and COVID-19 pandemic, but research on recent developments is scattered. We critically review recent literature on tele-MOUD and synthesize studies reporting primary data under four themes: clinical effectiveness, non-clinical effectiveness, perceptions, and regulatory considerations. Recent Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Changes in service delivery were also echoed by clients of the programs included in this study, particularly the flexibility in take-home MOUD doses and use of telehealth (Saloner et al, 2022), as well as in other studies conducted with people who use drugs during the same time period of the COVID-19 pandemic when this study was conducted (Krawczyk et al, 2021; Mahmoud et al, 2022). Despite this, nearly half the sites in this study reported reduction in funding during this period, while nationally there was an increase in opioid overdose (American Medical Association, 2022; National Center for Health Statistics, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Changes in service delivery were also echoed by clients of the programs included in this study, particularly the flexibility in take-home MOUD doses and use of telehealth (Saloner et al, 2022), as well as in other studies conducted with people who use drugs during the same time period of the COVID-19 pandemic when this study was conducted (Krawczyk et al, 2021; Mahmoud et al, 2022). Despite this, nearly half the sites in this study reported reduction in funding during this period, while nationally there was an increase in opioid overdose (American Medical Association, 2022; National Center for Health Statistics, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, interviews were conducted before the COVID-19 pandemic. Although healthcare systems have changed and new methods of engagement, such as telehealth (Mahmoud et al, 2022), emerged during the pandemic, our participants were able to convey their experiences to obtain an understanding of how this population engages in their healthcare for their complex needs.…”
Section: Moud Stigmamentioning
confidence: 99%
“…This shift may have been helpful for individuals with OUD [25, 26], many of whom experience barriers to health care due to intersecting effects of criminalization, discrimination, and social marginalization [13]. Virtual care allows clinicians to deliver essential healthcare services to PWOUD [27, 28], offering improved accessibility [29] and the ability to deliver OAT [30], while reducing barriers related to transportation, mobility limitations, and stigma [31]. However, virtual visits may limit clinicians’ ability to fully assess patients’ physical and emotional wellbeing [27] and may introduce technological barriers for those with limited internet access and low digital literacy [32, 33].…”
Section: Introductionmentioning
confidence: 99%